IMPLEMENTASI KEBIJAKAN INTEGRASI KURIKULUM PESANTREN DAN KURIKULUM NASIONAL DALAM MENINGKATKAN KUALITAS LULUSAN DI PONDOK PESANTREN AL MUKMIN NGRUKI - Fi Betsi Silviahadi; Rido Kurnianto; Syamsul Arifin (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
This article aims to analyze the implementation of policies integrating the pesantren curriculum and the national curriculum to improve the quality of graduates at Pondok Pesantren Al Mukmin Ngruki. The study employs a qualitative approach using a case study design. The research subjects consist of pesantren leaders, curriculum administrators, and educators selected through purposive sampling. Data collection techniques included in-depth interviews, participatory observation, and a documentary study of curriculum documents and learning activities within the pesantren environment. Data analysis was conducted through a systematic process of data reduction, data presentation, and drawing conclusions. The research findings indicate that curriculum integration at the Al Mukmin Ngruki Islamic Boarding School is achieved by aligning the national curriculum with the boarding school’s curriculum within a single integrated learning system. This integration is realized through the organization of the curriculum structure, the management of the academic schedule, and the implementation of teaching methods that link academic content with Islamic values. Furthermore, the implementation of curriculum integration is supported by curriculum management that involves coordination among the boarding school leadership, curriculum administrators, and educators in the planning, implementation, and evaluation of the curriculum. This study concludes that the integration of the boarding school curriculum and the national curriculum can serve as an effective strategy for enhancing graduate quality by combining academic competencies with the character development of students within a unified educational system.